International Trade Statistics Yearbook 2021, Volume II - United Nations Department of Economic; Social Affairs (United Nations, 2023)
This report contains detailed tables showing international trade for 258 individual commodities, for the 11 main Extended Balance of Payments Services categories, and world/regional trade tables or figures presenting statistics up to the year 2021. The information in the publication is based on data provided by approximately 175 countries (or areas) in the world. For more detailed data, users are requested to go to UN Comtrade (http://comtrade.un.org) which is the source of the information presented in the Yearbook and is continuously updated. The publication is aimed at both specialist trade data users and common audience at large. The presented data, charts and analyses will benefit policy makers, government agencies, non-government organizations, civil society organizations, journalists, academics, researchers, students, businesses and anyone who is interested in trade issues. The information and analyses are presented in a way which can be comprehended by non-expert users of statistics.